The Retail Value Chain: Howtogaincompetitiveadvantagethrough EfficientConsumerResponse(ECR)strategies - Sivonen, Hanna (LondonandPhiladelphia, 2012)
The internationalization and consolidation of retailing is turning the traditional retail industry on its head. International purchasing, fast and efficient operational models and new technologies constantly challenge retailers.